Multi-parametric magnetic resonance imaging assessment of whole tumour heterogeneity for chemoradiotherapy response prediction in rectal cancer. (April 2021) - Pham, Trang Thanh; Liney, Gary; Wong, Karen; Henderson, Christopher; Rai, Robba; Graham, Petra L.; Borok, Nira; Truong, Minh Xuan; Lee, Mark; Shin, Joo-Shik; Hudson, Malcolm; Barton, Michael B.
Highlights: Diffusion weighted imaging of heterogeneity can aid selection for 'watch-and-wait'. Apparent diffusion coefficient 75th and 90th quantiles were predictive of response. Dynamic contrast enhanced imaging did not add value in response prediction. Functional mapping of tumour heterogeneity may be used for targeting. Abstract: Background and purpose: Prediction of chemoradiotherapy response (CRT) in locally advanced rectal cancer would enable stratification of management. The purpose was to prospectively evaluate multi-parametric magnetic resonance imaging (MRI) assessment of tumour heterogeneity combining diffusion weighted imaging (DWI) and dynamic contrast enhanced (DCE) MRI for the prediction of CRT response in locally advanced rectal cancer. Materials and methods: Patients with Stage II or III rectal adenocarcinoma undergoing neoadjuvant CRT and surgery underwent MRI (DWI and DCE) before, during (week 3), and after CRT (1 week before surgery). Patients with histopathology tumour regression grade (TRG) 0–1 were classified as responders, and TRG 2–3 were classified as non-responders. A whole tumour voxel-wise technique was used to produce apparent diffusion coefficient (ADC) and K trans (Tofts model) histograms derived from DWI and DCE-MRI, respectively. Logistic regression was used to predict response status for ADC and K trans quantiles. Results: Thirty-three patients were included in this analysis; 16 responders, and 17 non-responders. On heterogeneity analysis, odds of being a responder were significantly higher after CRT (before surgery) for higher ADC 75th (p = 0.049) and ADC 90th (p = 0.034) percentile values. The K trans quantiles were lower in non-responders than responders before and during CRT, and higher after CRT although no significant association with response status was observed (p ≥ 0.10). Conclusions: DWI-MRI after CRT (before surgery) incorporating a histogram analysis of whole tumour heterogeneity was predictive of CRT response in patients with locally advanced rectal cancer. DCE-MRI did not add value in response prediction. Clinical trial registration: Australian New Zealand Clinical Trials Registry (ANZCTR) number ACTRN12616001690448.